Reflections of Social Development in Fivefold Project Law about Economy, Social and Cultural in Islamic Republic Iran from 1989-2015 - ali ghovati sefidsangi; hoseyn farashiyani; hossein hasan zadeh choocanlu (توسعه اجتماعی, 2017)
Social development is undoubtedly a multifarious process that involves a series of factors, including political, economic-social, cultural and legal as well as multi-level set of activities that have role the government and institutions, civil society and even the international community. In this research, examine social development, with emphasis on both Welfare and humanistic development, the laws of development of the first, second, third, fourth and fifth from 1989 to 2015, to determine what approach to development social development, and what are your strengths and weaknesses? In this regard, the two indicators: Welfare and humanistic used to assess social development. The research method is quantitative content analysis. In this study statistical population are all the program of first to fifth development law and because examine have not any sampling; the results shows that all the development projects was emphasis to welfare development indictors and has been neglected indicators of humanitarian. The most poorly rated program، is the first program development.